Gender Equality Provided by Active Action in Recruitment and Selection Process - Tatár-Kiss, Klára (Marketing & Menedzsment, 2021)
THE AIM OF THE PAPER Despite all the efforts in relation to hiring women to workplaces, parity has not yet been achieved, and the gap between women and men is even wider when leadership roles are considered. Organizations are gendered, the human resource practices are outdated and are still structured around the ideal, male worker. The main objective of this paper is to critically review the recruitment and selection process (RSP) and provide active actions as practical recommendations, which will enable organisations to hire women into the workplaces. METHODOLOGY This research is an empirical study of large multinational organizations, identifying the key human resource policy intervention points in the RSP. MOST IMPORTANT RESULTS The outcome of the critical review is that the traditional RSP needs to be transformed and only this transformation – applying positive actions - will enable organisations to achieve gender equality at the workplace. The novelty of this paper is the empirical research of global organizations, based on which, the key intervention points of RSM were identified. The following active actions are proposed: embed employer branding and early talent attraction into the recruitment process; provide transparency of salary bands; apply of female quotas; use structured interviews; run diverse interview panels; and use explicit comparator method.